Artificial Intelligence in Public Health: Bridging Today’s Trends with Tomorrow’s Possibilities - Daniele Giansanti; Giovanni Costantini (Bioengineering)
Driven by the unprecedented challenges of the COVID-19 pandemic, the healthcare sector has witnessed remarkable—and at times sometimes overwhelming—advancements in the role of artificial intelligence (AI) [...]